Investigating the Implications of Online Health Information Seeking and Prevalence of Cyberchondria Amongst Patients Visiting Emergency Departments - Rutty, Danielle Paige (Université d'Ottawa / University of Ottawa, 2023)
Finding health information online continues to help patients understand new symptoms. However, incomplete information or advice that errs on the site of caution can cause distress or anxiety and prompt visits to a doctor. Cyberchondria, a new phenomenon, is defined as excessive compulsive searching for health information online that leads to distress and increase utilization of healthcare services. Grounded theory guided the conception of a mixed method study to investigate cyberchondria and symptom appraisal within Emergency Departments. A questionnaire and interviews were used to collect data from patients visiting a local Emergency Room. Results showed 63.3% of respondents looked up their symptoms online before their visit, and exhibited higher levels of cyberchondria and health anxiety than those who did not (p .001, p .004), and that health information consulted online can impact the decision to seek out immediate care. Strategies are needed to improve and promote quality online sources to benefit both seekers and services.
Keywords: online health information seeking; Symptom appraisal; Cyberchondria; emergency department utilization; questionnaire; interviews; case study; eHealth communication